(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
In this article, the main problems of literary texts in the world and Russian linguistic traditions, using methodologies and theoretical foundations, specific ideas are presented. The evolution of these traditions demonstrates the rich relationship between structural form and sociopragmatic content, and is a product that illuminates the multifaceted ways literature reflects and shapes human experience.